Closing the knowledge gap : integrated water management for sustainable agriculture (CTA AJ WagenengenNL, 2010)
Aims to find out what were the key informaiton and knowledge needs that underpin efficient water resource use for improved agricultural productivitity and growth in ACP countries.
Keywords: WATER MANAGEMENT